Determination of Empirical Formula Model of Soil Vibration Acceleration of Denpasar Area - Priyanto, Dwi Karyadi; Suarbawa, K.N.; Septiadhi, Ardhianto (BULETIN FISIKA; Vol 19 No 1 (2018): BULETIN FISIKA, 2018)
In this research, we have determined the model of empirical formula of Peak Ground Acceleration (PGA) based on general formula of Lin and Wu using 62 observational PGA data which corresponds to earthquake parameter data of Bali and its surroundings for year 2008-2013. Based on the regression analysis, the geometrical spreading coefficient is a = -2.019, the magnitude coefficient b = 0.894, the empirical model formula constant c = 0.551, and the empirical model of PGA model for Denpasar is. The results of statistical verification yielded a strong positive linear correlation of 0.853 with the residual error of 0.035.